The Gap between Lifetime Fertility Intentions and Completed Fertility in Europe and the United States: A Cohort Approach - Éva Beaujouan; Caroline Berghammer (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
We study the aggregate gap between intended and actual fertility in 20 countries in Europe and the United States, adopting a cohort approach that differs from the period approach widely used in prior research. We compare the mean intended number of children and percentage intending to be childless among young women aged 25-29, measured during the 1990s, with the data on completed or almost completed fertility in the same cohorts later in life when they were aged 40 and older. In addition, we analyze the aggregate intentions-fertility gap among women with different educational attainment. Our exploration is informed by the cognitive-social model developed by Bachrach and Morgan (2013). The results reveal distinct regional patterns with regard to the completed fertility-intentions gap, most apparent for the childlessness gap. In addition, the gap is the largest among highly educated women in most studied countries and its educational gradient also varies by region.
Keywords: 300; Fertility; childlessness; lifetime intentions; gap; education; Europe; United States